2017
DOI: 10.1177/2380084417699400
|View full text |Cite
|
Sign up to set email alerts
|

Resin Infiltration of Caries in Primary Molars in a Community Setting: 24-Month Randomized Controlled Trial Findings

Abstract: These study findings can help clinicians decide which caries management approach they wish to use to prevent progression of proximal lesions in primary molars. With consideration of cost and patient preference, this information could lead to more appropriate therapeutic decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…They reported adequate concealment measures for random allocation of intervention and control/placebo to NCPLs. Such measures were placing the random sequence inside sealed envelopes[171819] and letter coding of each NCPL management strategy,[20] whereas the remaining three studies did not report any means of allocation concealment and therefore were judged to have an unclear risk of bias. However, they were not excluded because this was not likely to affect the outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported adequate concealment measures for random allocation of intervention and control/placebo to NCPLs. Such measures were placing the random sequence inside sealed envelopes[171819] and letter coding of each NCPL management strategy,[20] whereas the remaining three studies did not report any means of allocation concealment and therefore were judged to have an unclear risk of bias. However, they were not excluded because this was not likely to affect the outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported all the prespecified outcomes and therefore were judged to have a low risk of bias. [1718192223] In contrast, two trials were at high risk of bias since they failed to mention all their prespecified outcomes. Ekstrand et al [20] did not report the results of their 6-month clinical assessment, and the radiographic evaluation was incomplete.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining five studies assessed lesions in primary teeth (261 patients, 522 lesions) [ 63 , 64 , 65 , 66 , 67 ]. Follow-up ranged between 12 to 24 months (median: 24 months) with a yearly drop-out of 2–11% (median: 10%).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis by Chen et al in 2021 concluded that although more clinical studies were needed, findings from current studies were encouraging and resin infiltration is efficacious in arresting decay progress in primary teeth for 12–24 months [ 130 ]. Based on these studies, the therapeutic effect of RI was found to range from 21% [ 134 , 135 ] to 38% [ 136 ].…”
Section: Resin Infiltration For the Management Of Carious Lesionsmentioning
confidence: 99%